An Appraisal of Selected Teachings and Practices of the Church of Christ in South Western Nigeria (2014)
The Church of Christ (COC), established in South-western Nigeria in 1959 as an offshoot of the 19th century sectarian American Restoration Movement, claims to be the only true church to restore primitive Christianity in both teachings and practices. Contrariwise, evidence from Early Church history contradicts this claim, which necessitates an investigation into the true position; existing studies having focused on the history of the church and the biographies of its leaders to the neglect of the appraisal of the claims of the church in terms of conformity with the teachings and practices of the Early Church. This study, therefore, makes a comparative appraisal of selected tenets of COC in South-western Nigeria against the backdrop of the Early Church with a view to examining the validity of its claims. The study adopted the descriptive research design. In-depth interviews were conducted with purposively selected clergy (36; six from each state of South-western Nigeria) and laity (36; six from each state). Church records were consulted in six (one from each state) congregations of the church to complement the interviews. Published Early Church records were also consulted. Data were subjected to historical and comparative analyses. There were three teachings of COC: exclusive claim to being the true church; the belief in theology, but non-celebration of Christmas and Easter which were believed to be absent in the Early Church era; and non-belief in miracles after the apostolic age. Three practices were also distinguished: non-use of musical instruments in worship, absolute congregational autonomy and alienation from other Christian denominations. Attestations from Early Church writings revealed that COC has no antecedent in post-apostolic Christianity; but archival sources showed that the church emerged from the 19th century religious aftermath of American independence premised on democratic theology. The COC’s teachings on non-celebration of Christmas and Easter were nullified by evidence from Early Church writings confirming Easter as the oldest Christian festival and that Christmas celebration had its origin in the Early Church. The teaching that miracles ceased with the apostolic age was negated by evidence from the Didache (A.D. 110) and testimony of St. Augustine (A. D. 354-430). Conversely, COC’s A cappella practice was confirmed from the writings of Justin Martyr (A.D. 100-165) and Tertullian (A.D. 160-220) that musical instruments were seen as corruptive influence of the Roman culture. On absolute congregational autonomy, Ignatius (A.D. 50-110) and Eusebius confirmed that Episcopacy was in practice from the second century. Contrary to its anti-ecumenical disposition, Early Church records confirmed that ecumenical councils were convened starting from Nicea (A.D. 325) to define the substance of the Christian faith and defend it against heresy. All the teachings of the Church of Christ are at variance with those of the Early Church; one out of the three practices aligned with that of the Early Church. Thus, there is a wide disparity between the tenets of the two churches, which invalidates the church’s exclusive historical connection with the Early Church. Therefore, the church needs to own up to history and reappraise her hermeneutical presuppositions